2020
DOI: 10.7759/cureus.8753
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Disappearing Calcifications in the Breast: A Rare Instance Where a Decrease in Size on Mammogram Is Not Good

Abstract: Spontaneously resolving breast calcification on mammography is a rare radiologic finding. This phenomenon is defined by a decrease in number and/or prominence of breast calcifications on mammogram when compared to prior imaging. The significance of resolving breast calcifications remains unclear, but they have been reported in cases of malignancy. In current literature, patients whose imaging illustrated a decrease in calcifications usually had other concomitant breast complaints. We are presenting a case of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Information about the size, density, and distribution of breast microcalcifications can give an idea about the benign or malignant nature of cancer. It is found that decreasing calcifications is not a benign finding on mammogram [19]. Spontaneous decreases in calcifications are not necessarily indicative of better clinical outcomes.…”
Section: Importance Of Small-sized Segments In Medical Imagesmentioning
confidence: 90%
“…Information about the size, density, and distribution of breast microcalcifications can give an idea about the benign or malignant nature of cancer. It is found that decreasing calcifications is not a benign finding on mammogram [19]. Spontaneous decreases in calcifications are not necessarily indicative of better clinical outcomes.…”
Section: Importance Of Small-sized Segments In Medical Imagesmentioning
confidence: 90%
“…Studies reported some variabilities in the screening results with this modality, facing various clinical factors such as age, breast density, type of malignancy, and family history [3][4][5][6][7]. Fibrocystic breasts, hormone replacement therapy, and dense breasts undermine the strength of mammography imaging for accurate diagnosis (and screening) [8][9][10][11]. As an alternative, magnetic resonance imaging (MRI) is often used as it is relatively expensive and has lower specificity than mammography [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Mammography has been the gold standard for diagnosing breast cancer since the early 1960s despite numerous studies indicating the variability of this imaging modality is affected by breast density, age, type of problem, and family history [2][3][4][5]. Mammography showed weakness in being used for breast cancer screening for women with dense breasts, hormone replacement therapy, and fibrocystic breasts [6][7][8][9]. Research showed the detection rate of mammography considerably diminishes by increasing breast density among the patients [7].…”
Section: Introductionmentioning
confidence: 99%